Upconversion Nanoparticles for Cancer Therapy. Issue 12 (26th October 2022) - Li, Yang; Chen, Guanying
Abstract : Lanthanide‐doped upconversion nanoparticles (UCNPs) are anti‐Stokes emitters, which can produce higher‐energy ultraviolet/visible and near‐infrared (NIR) luminescence when excited with low‐energy NIR light. They are featured with nonphotobleaching, sharp emission peaks, superstability, low toxicity, low imaging background, and functional multimodality. These characteristics endow them to be useful as nanoprobes for diagnostic applications and imaging‐guided cancer therapy. Importantly, the ability to convert tissue‐penetrating NIR light into visible and ultraviolet range can expedite Fenton‐ or Fenton‐based processes in chemical dynamic therapy (CDT), activate photosensitizers (PSs) to produce singlet oxygen in photodynamic therapy (PDT), and regulate light‐controlled drug delivery processes for efficacious cancer therapy. The past decade witnessed fast progress of UCNPs as agents in single‐mode therapy or combined therapies in the forefront researches on fighting cancer. This review summarizes the fundamental roles of UCNPs in cancer therapy, highlights types of cell deaths induced by excessive reactive oxygen species (ROS), and showcases cutting‐edge applications in combined cancer therapies as well as imaging‐guided cancer therapy. Challenges and outlook on the use of UCNPs for future directions in cancer therapy are also discussed. Abstract : Lanthanide‐doped upconversion nanoparticles (UCNPs) have exceptional properties that make them suitable for use as nanoprobes in diagnostic applications or imaging‐guided cancer therapy. This review summarizes the fundamental roles of UCNPs in cancer therapy, highlights types of cell death caused by excess reactive oxygen species (ROS), and highlights cutting‐edge applications in multimode cancer therapy and imaging‐guided cancer therapy.